ANALISIS PRODUKSI NILAM DAN NILAI TAMBAH PENYULINGAN MINYAK ATSIRI DI KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Juniardi, Mohammad Taufik Hardian (JSTT, 2015)
The purpose of this study was to; (1) To determine the effect of production inputs of land, seed, fertilizer urea, liquid fertilizer, and labor on farm production patchouli in Donggala District of South Banawa, (2) To determine the value added in the oil refining business in the District of South Banawa District Donggala. The research was conducted in January to April 2015. The population in this study farmers who grow patchouli patchouli in the District of South Banawa, amounting to 120 people and business owners distillation of patchouli, amounting to 1 person. Sampling in this study using a random method (simple random sampling). The number of samples taken patchouli farmers as many as 36 people, owners and labor 6 oil refining business, so the total number of samples as many as 43 people. Based on the results of the analysis showed that simultaneous (Test-F) Xi variables significant at Î± = 5%, while the partial all input variables used significant effect on production (Y). These variables are the land area (X1), patchouli seeds (X2), urea (X3), liquid fertilizers (X4) and labor (X5). Based on these results indicate that the patchouli farming in South Banawa Regional District of Donggala been rational, meaning that the use of existing production inputs is optimal, so that the results can be maximized. Value added is the difference between the value of output, the contribution of other inputs and raw material prices. The income of added value by oil refining business in the District of South Banawa Rp 3,257 means that for every 1 kg of raw material will generate output patchouli essential oil of Rp 3,257/production process and the ratio of added value to the output value is 36.19 with the understanding that every 1 kg of patchouli essential oil will be processed into value-added gain of 36.19%.